Early treatment-seeking behaviour for malaria in febrile patients in northwest Ethiopia - Workineh, Baymot (Malar J, 2018)
BACKGROUND: As malaria is among the leading public health problems globally, early diagnosis and treatment of cases is one of the key interventions for its control and elimination. Nevertheless, little is known about early treatment-seeking behaviour for malaria of people in Ethiopia. This study was conducted to investigate early treatment-seeking behaviour and associated factors among febrile patients in Dera district, one of the malaria hotspot districts in Ethiopia. METHODS: An institution-based, cross-sectional study was conducted among malaria-suspected febrile patients in Dera district, Amhara Regional State, Ethiopia from September to December 2017. The study used the lottery method to select sample health facilities, and participant allocation to facilities was done in proportion to client flow to the respective health facilities. Data were collected by interview. Thus, binary logistic regression model was fitted to the data. Crude and adjusted odds ratios with the respective confidence intervals and p-values were computed. An explanatory variable with a p-value ≤ 0.05 was considered statistically significant. SPSS version 20 was used for the analysis. RESULTS: A total of 680 respondents completed the study with a response rate of 96.6%. The study revealed that 356 (52.4%) participants sought treatment within 24 h of fever onset, and patients who: knew the advantage of sleeping under nets [AOR 95% CI 2.8 (1.70–4.60)]; knew mosquito breeding sites [AOR 95% CI 1.9 (1.10–3.30)]; had good, overall knowledge about malaria [AOR 95% CI 2.7 (1.56–4.76)]; had previous history of malaria [AOR 95% CI 3.26 (1.64–6.49)]; were at a distance of < 6 km from a health centre [AOR 95% CI 2.5 (1.72–3.60)]; and, had family size < 5 [AOR 95% CI 2.1 (1.43–3.20)], were more likely to seek treatment within 24 hof fever onset. CONCLUSION: A low proportion of malaria-suspected patients sought treatment within 24 h of fever onset compared to the national target. Awareness about the advantage of sleeping under nets, knowledge about mosquito breeding sites and malaria itself, previous history of malaria, distance from the health centres, and family size were found to be predictors of early treatment-seeking behaviour for malaria. Strengthening strategies tailored to increasing awareness for communities about malaria prevention methods and early treatment-seeking behaviour is essential.